Phase-selection algorithms to minimize cost and imbalance in U.S. synthetic distribution systems. (September 2020) - Postigo, Fernando; Mateo, Carlos; Gómez, Tomás; de Cuadra, Fernando; Dueñas, Pablo; Elgindy, Tarek; Hodge, Bri-Mathias; Palmintier, Bryan; Krishnan, Venkat
Highlights: Existing test feeders do not allow testing new algorithms in large-scale systems. The RNM-US is a planning tool that generates distribution systems from scratch. The synthetic distribution systems are large-scale. The proposed algorithms allow designing multiple phase feeders. The specific phases of the network components are selected to minimize unbalance. Abstract: The increasing penetration of distributed energy resources (DERs) has driven a push toward new algorithms and tools for distribution system operation and planning; however, there is a lack of publicly available electrical distribution test systems at the large scale—multi-feeder, multi-substation—which are required for realistically evaluating the performance and scalability of these new developments. This paper presents a Reference Network Model (RNM) aimed to plan large-scale, U.S.-style, synthetic distribution systems. Special emphasis is placed on two algorithms that allow multi-phase feeder design: (1) a method to select the most suitable number of phases for each section considering the connected customers, and (2) a method to assign phases to the users to provide near-balanced phasing while maintaining realistic levels of imbalance. The performance of the developed algorithms is verified by comparing the obtained system designs with the original IEEE 8, 500-node test feeder and the Electric Power Research Institute (EPRI) J1 feeder.